The life of Harriot Stuart, written by herself - Lennox, Charlotte 1729-1804 (Fairleigh Dickinson Univ. Press [u.a.], 1995)
In addition to its importance to the study of the development of Lennox as a novelist, Harriot Stuart is significant as well for its heroine who, while possessing many of the outward characteristics of the sentimental heroine of the day, ultimately breaks with this tradition to stand as a model for the strong, passionate, and individualistic heroines who were to become so important to the English novel in the second half of the eighteenth century and beyond